Perancangan Media Pembelajaran Interaktif Konsep Dasar Seluler Menggunakan Aplikasi Unity Berbasis Android - Dio Alvendri; Yasdinul Huda; Resmi Darni (Departement of Mathematics Education, 2023)
Telecommunication is the most important thing in this era of globalization, there are many ways to transfer information both conventionally and with the help of technology, the use of technology can be online or offline in the current era of digitalization, there have been many developments in telecommunication networks passed, the development of this cellular network has evolved from 1G, 2G, 3G even 4G, the